Pengendalian RKPG dan Pendampingan Pemerintah Gampong Melalui Kemitraan BAPPEDA di Kecamatan Meurebo, Aceh Barat - Nellis Mardhiah; Ikhsan Ikhsan; Said Achmad Kabiru Rafiie (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
The term Gampong means village which is a division of administrative territory in the province of Aceh, Indonesia. Thus, the Village Development Work Plan (RKPG) which is an obligation in the governance of the development of the Village of Gunong Kleng for the sake of community life. This RKPG becomes the obligation of the regional government in guiding the Gampong government apparatus in development management in accordance with applicable regulations. The general objective of this service is to build a good partnership between BAPPEDA and the Gampong government in realizing the regional development strategic plan through a bottom-up approach in sustainable development plans. Specific objectives in this service activity consist of, First; to enhance BAPPEDA and Gampong Government partnerships in Development planning; Secondly, it can realize the village development plan in accordance with the results of the musrenbang; Third, the implementation of development can be controlled through the document form RKPG provisions that have been determined in accordance with applicable regulations. The assistance model in the community service activities for the Gampong community to be able to fulfill the program of this activity can be carried out through 4 (four) stages, namely the FGD on the RKPG and RPJMG provisions, the Socialization of the MURENBANGDES Implementation Mechanism, the implementation of a social control mechanism that is directly imposed by the community in accordance with the RKPG provisions. The results of community service assistance are carried out through a bottom-up development model approach in the RKPG in the village of Gunong Kleng to plan the development of the Gampong in accordance with the Gampong RPJMG that has been set. Implementation of the development can increase community participation, and can increase the value of community trust in the Gampong government in governance. development in a transparent, accountable and sustainable development in Gampong Gunong Kleng, West Aceh.